Coconut-water as fermentation medium for enzyme production (3): Optimisation of batch 5L stirred tank fermentation - Ahmad Jaril Asis,; Jailani Salihon, (1995)
The enzyme volume yield (nmol L-1) in batch 5L stirred tank fermentations for the production of the enzyme cytochrome p-450 by the yeast Saccharomyces cerevisiae NCYC. 754 on a medium based on coconut water was optimised with respect to the experimental variables temperature (T), pH and stirring rate (RPM), which were all under constant set point control, using the 23factorial experiments and steepest ascent methods to locate the area containing the maximum enzyme volume yield and using a rotatable composite design to find the optimum levels of the experimental variables at the point of maximum yield. It was found that for maximum enzyme volume yield the levels of the variables are as follows: T = 26.88° C, pH = 5.12 and RPM = 253 rpm. Experiments conducted with these optimised levels of variables gave an average enzyme volume yield of 637.36 nmol L-1. This represents an improvement of 71% compared to the maximum yield in shake-flask fermentation of 372.62 nmol L-1